2006
DOI: 10.1517/17425255.2.2.261
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to xenobiotics in the skin: from contact sensitivity to drug allergy

Abstract: Skin is the most frequent target of adverse drug reactions. These cutaneous drug reactions (CDRs) show varied clinical manifestations ranging from mildly discomforting rashes to life-threatening Stevens-Johnson syndrome or toxic epidermal necrolysis. Most CDRs appear to be immune mediated, although the mechanism by which they are initiated remains unclear. In this review, current knowledge of the mechanisms by which xenobiotics provoke immune responses in the skin after epicutaneous administration and how simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 111 publications
0
6
0
Order By: Relevance
“…This potentially contributes to the clinically observed toxicities. Little is known about ERL-induced Stevens-Johnson syndrome and toxic epidermal necrolysis, but these syndromes are considered immunogenic, are commonly drug-induced, and drugs commonly associated with initiating these toxicities do not share common targets (Khan et al, 2006). Many compounds that are reported to induce Stevens-Johnson syndrome are associated with metabolic activation to form reactive intermediates, such as carbamazepine, diclofenac, penicillin, modafinil, acetaminophen, ibuprofen, and phenytoin (Neuman and Nicar, 2007;Locharernkul et al, 2008;Levi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This potentially contributes to the clinically observed toxicities. Little is known about ERL-induced Stevens-Johnson syndrome and toxic epidermal necrolysis, but these syndromes are considered immunogenic, are commonly drug-induced, and drugs commonly associated with initiating these toxicities do not share common targets (Khan et al, 2006). Many compounds that are reported to induce Stevens-Johnson syndrome are associated with metabolic activation to form reactive intermediates, such as carbamazepine, diclofenac, penicillin, modafinil, acetaminophen, ibuprofen, and phenytoin (Neuman and Nicar, 2007;Locharernkul et al, 2008;Levi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, knowledge of the mechanisms of T cell-mediated allergies to orally or parenterally administered drugs is still only limited because of the variety of the clinical presentations of drug-induced diseases and of the lack of appropriate experimental models. Therefore, the mechanisms by which haptens provoke ACD after epicutaneous administration have served as a paradigm of how similar reactions to haptens may occur after systemic routes [56].…”
Section: Pathophysiology Of T Cell-mediated Drug Allergymentioning
confidence: 99%
“…Many drugs are known to provoke immune responses in the skin when applied topically or administered systemically. Studies of contact sensitivity have shown the importance of immune events in the skin itself for the provocation of a hypersensitivity reaction in the skin (Khan et al, 2006). Essential for initiation of such reactions is the activation of resident dendritic cells (i.e., LCs).…”
Section: Clinical Implications Of Drug Metabolism In Skinmentioning
confidence: 99%